RELASI AGAMA DAN NEGARA: ANALISIS POLITIK NURCHOLISH MADJID - Lismijar Lismijar (Lembaga Studi Agama dan Masyarakat Aceh (LSAMA), 2017)
Islamic political movements have always given rise to tensions in many ways, especially in state and religious discourses. Some have argued that Islam is a unity that has an inseparable socio-political type. This opinion is reinforced by the real doctrine of Islam is religion and State. Meanwhile, Islam is more inclined to interpret the nature of Islamic universality in a more substantialistic direction. Such a tendency puts more emphasis on the content than just political containers whose political practice is not aimed at establishing a political structure characterized by the formal formation of the Islamic state, but rather a political ethic and morality inspired by the substance of Islamic teachings. Nurcholish Madjid as a Muslim intellectual who colored Islamic reform in Indonesia, tried to offer a new way for the achievement of the nation's collective ideals. Nurcholish Madjid's deep concern over the objective conditions of the nation encouraged him to seriously reflect the national problem by engaging in Islamic political expression in the form of Islamic political thought. Islamic political thought Nurcholish Madjid gives more democratic values and pluralism as the goal of creating more Islamic politics to the content of the form. Therefore, the purpose of this study is to know the concept of religion, the existence of national state and religious and state relations in the perspective of Nurcholish Madjid. In conducting this study, the authors used a qualitative descriptive approach by collecting main data through library research (library research). Technique of collecting data obtained through primary data and secondary data. This research uses descriptive analysis methodology. The results of this study indicate that there are several discourses presented by Nurcholish Madjid on religious and state relations, among them the Islamic discourse with the national state, Islam and Pancasila, Islam and democracy and Islam and pluralism. Prior to addressing the discourse of the relationship between the discourse of Islamic relations with the national state, he first threw the jargon of